A multi-phase mesoscopic simulation model for the long-term chloride ingress and electrochemical chloride extraction. (8th February 2021) - Chen, Xuandong; Fu, Feng; Wang, Hai; Liang, Qiuqun; Yu, Aiping; Qian, Kai; Chen, Ping
Abstract: Electrochemical chloride extraction (ECE) is one of the effective methods to remove chloride and prolong the service life of reinforced concrete (RC) structures. To fully understand the mechanisms of the long-term chloride ingress and subsequent ECE treatment of RC structure, a multi-phase mesoscopic numerical model is proposed. Unlike most of existing models, the long-term chloride ingress and the effect of chloride binding are considered in the proposed model, and the transport of chloride is simulated through a novel diffusion-migration-reaction process. The numerical simulation results show that the adsorption capacity of concrete to chloride decreases with the increase of chloride ingress time. Interestingly, the free chloride concentration on the surface of concrete decreases dramatically, and the maximum value appears in the concrete protective cover after ECE treatment. Furthermore, ECE treatment time, current density and concrete protective cover have significant influences on ECE treatment efficiency. Besides, the quantitative relationship models between these factors and ECE treatment efficiency have been developed. Moreover, the use of stirrup can improve the efficiency of ECE treatment. The research outcomes reveal previously ignored fundamental aspects of the ECE treatment and provide insights for the durability prediction of RC structures.